Educational Transformational Leadership - Sukatin , Sukatin; Hariyanto, Mashudi; Sholehah, Juliana; Indah, Rosa; Latifah, Suci; Hardi Ramadhani, Sigit (PT Literasi Nusantara Publisher, 2022)
Education is a parameter of the progress of a nation. The essence of education will make the direction of development for human resources competence and potential optimized. Utilization of a large number of human resources by comprehensively improving the education system at the national level. Improvement of the education system began at the primary and secondary education levels, high school level education, and tertiary education. A change in the educational paradigm is a must towards a new world order pattern that is more humane and democratic. Differences in education patterns in Indonesia's regions which include urban, hinterland and rural areas will show the quality of the education system. The portrait of education in Indonesia in almost every region is getting blurrier day by day. This is because education in Indonesia adheres more to diploma and economic interests. Education is not to educate the public, but as an understanding of interests. So that the resulting education system is not a static change, but is dynamic with changes in government.